Differences in U14 football players’ performance between different small-sided conditioned games - Clemente, Filipe M. (2015)
The aim of this study was to determine the effects of different formats and task conditions in small-sided conditioned games (SSCG) on young soccer players’ heart rate responses and time-motion profiles. Ten young male soccer players (age: 14.6 ± 0.8 years old; and years of practice: 4 ± 1.2) from a regional league were tested. Each player played in two different formats namely 1 versus 1 with another 1 neutral player (i.e., 1v1+1) and 2 versus 2 with another 1 neutral player (i.e., 2v2+1), and three task conditions (T1 – no goal, T2 – no goal but endline, T3 – goal. Each SSCG lasted for 3 minutes with 3 minutes of passive recovery between SSCG. The heart rate responses, distance coverage, speed and acceleration were recorded throughout all SSCG. Results show that the format (F(4,5403) = 509.025; p-value = 0.001; n2 p = 0.274; Power = 1.000; moderate effect size) and task conditions (F(8,10808) = 33.714; p-value = 0.001; n2 p = 0.024; Power = 1.000; small effect size) were both significant factors on performance variables. The different formats and task conditions used in this study enable coaches to carry out a more specific training, helping them to understand the real effects of each variable on players’ performance.